2021
DOI: 10.14745/ccdr.v47i03a04
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nonpharmaceutical interventions on laboratory detections of influenza A and B in Canada

Abstract: Background: The first coronavirus disease 2019 (COVID-19) case was reported in Canada on January 25, 2020. In response to the imminent outbreak, many provincial and territorial health authorities implemented nonpharmaceutical public health measures to curb the spread of disease. “Social distancing” measures included restrictions on group gatherings; cancellation of sports, cultural and religious events and gatherings; recommended physical distancing between people; school and daycare closures; reductions in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…In this study, we only observed one positive detection of influenza A in a wastewater sample from a major Canadian city and no detection of influenza B or respiratory syncytial virus. The lack of detection may be reflective of the low transmission rates of influenza and other respiratory viruses from 2020 to 2021 ( 41 43 ), or it may indicate that the GeneXpert is not suitable for surveillance of these pathogens, warranting further studies. Other clinical tests for the GeneXpert system have targets likely to be present in wastewater such as norovirus, Clostridium difficile , and various antimicrobial resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we only observed one positive detection of influenza A in a wastewater sample from a major Canadian city and no detection of influenza B or respiratory syncytial virus. The lack of detection may be reflective of the low transmission rates of influenza and other respiratory viruses from 2020 to 2021 ( 41 43 ), or it may indicate that the GeneXpert is not suitable for surveillance of these pathogens, warranting further studies. Other clinical tests for the GeneXpert system have targets likely to be present in wastewater such as norovirus, Clostridium difficile , and various antimicrobial resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review observed a lack of data from the Middle East, South East Asia, Western Pacific and Latin American regions regarding the number of acute respiratory cases sampled for influenza surveillance before the COVID-19 pandemic in 2019. Meanwhile, almost double the number of symptomatic cases were sampled as part of influenza surveillance during the current pandemic in Canada 11,17 . The WHO European region testing a large number of influenza samples reported a decline in surveillance samples during the COVID-19 pandemic and the lowest number of influenza types and subtypes were noted since the establishment of GISRS in 1952.…”
Section: Discussionmentioning
confidence: 99%
“…Many nonpharmacological epidemiological measures implemented during the COVID‐19 pandemic, including quarantining, wearing masks, social distancing, and frequent hand washing, are known to decrease influenza infections. 3 , 4 , 5 , 6 Furthermore, a recent study found that decreases in influenza infections were associated with the implementation and timing of COVID‐19‐related nonpharmacological interventions in China and the United States. 7 These nonpharmacological interventions could account, at least in part, for the decrease in influenza infections in the 2019–2020 and 2020–2021 seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Lagacé‐Wiens et al reported a decreased incidence of influenza during the COVID‐19 pandemic and reported that the weekly positivity rates declined from 20.16 to 0.11 during the COVID‐19 pandemic. 6 In our institution, an influenza test is ordered for influenza‐like illness seasonally. Consistent with the state and county trends, influenza testing and cases were higher in 2019–2020 seasons.…”
Section: Discussionmentioning
confidence: 99%